New insights into lignin electrolysis on nickel-based electrocatalysts: Electrochemical performances before and after oxygen evolution. (19th October 2021) - Beliaeva, K.; Grimaldos-Osorio, N.; Ruiz-López, E.; Burel, L.; Vernoux, P.; Caravaca, A.
Abstract: The production of H2 via electrolysis seems to be the best alternative to traditional catalytic reforming processes. The electrolysis of lignin allows to produce pure H2 while valorizing a low-price biomass waste with (theoretically) lower energy requirements than water electrolysis. Previous studies were published in the last years dealing with the electro-oxidation of lignin on Ni-based catalysts. Ni is a robust non-expensive metal that presents a wide variety of oxidation states and phase transitions. To this date, it is still not completely clear how these states/transitions activate the lignin molecule. The aim of this study is to get more insights into the cleavage of the main chemical bonds present in the complex lignin structure over different Ni oxidation states. A Ni/C catalyst, prepared by the polyol method, was thoroughly characterized and tested for the electro-oxidation of both, lignin and 2-phenoxyethanol, where the latter is a model molecule representative of the quintessential β-O-4 linkage in lignin. Highlights: Lignin electrolysis as a promising technology for H2 production. Electrochemical study with model molecule: Fundamental understanding. New insights into lignin electro-oxidation on different Ni phases/oxidation states.